Environmental impact evaluation and long-term rutting resistance performance of warm mix asphalt technologies. (1st January 2021) - Wu, Shenghua; Tahri, Omar; Shen, Shihui; Zhang, Weiguang; Muhunthan, Balasingam
Abstract: The adoption of warm mix asphalt (WMA) technologies is well accepted due to its promising environmental benefits, however, their long-term field performance is not well understood. This study focused on the long-term rutting resistance of WMA and their companion hot mix asphalt (HMA) based on 83 field samples collected from 28 field projects across the United States covering four climate zones, and quantified environmental impacts for various WMA technologies as compared to HMA. Field cores were evaluated by dynamic modulus, creep compliance, and Hamburg wheel-tracking device tests. Asphalt binders extracted from field cores were evaluated by continuous performance grading (PG), multiple stress creep recovery (MSCR), and monotonic shear tests. The results showed that WMA binders exhibited similar rutting resistance compared with the HMA binders after long-term field aging. Existence of polymer in the asphalt binder was displayed through the plot of non-recoverable creep compliance and percent recovery. The long-term field aged polymer modified asphalt binders for WMA and HMA were comparable. The results also showed that the CO2 reduction by using WMA ranged from 89.09% to 42.79% depending on WMA type. On average, the CO2 emission was reduced to 66.89% by using WMA technologies. Overall, environmental impact analysis and long-term field performance results validated the confident use of WMA technologies. Highlights: On average, the CO2 emission can be reduced to 66.89% by using WMA technologies. WMA binders exhibited similar rutting resistance compared with the HMA binders after long-term field aging. Environmental impact analysis and long-term field performance results have validated the confident use of WMA technologies.